GE_GERICHTE C/25777/2015 vom 10. Juni 2016 - GE Cour de justice (2016)
OBLIGATION D'ENTRETIEN ; MAINLEVÉE DÉFINITIVE ; EXTINCTION DE L'OBLIGATION ; COMPENSATION DE CRÉANCES | LP.80; LP.81; CO.125; CO.120;